The Relationship of Food Intake and Mother's Parenting Patterns With the Incident of Stunting in Toddlers - Annisa Febriana (STIKES Columbia Asia Medan, 2024)
Stunting occurs when a child's height is lower than average age due to poor growth caused by chronic malnutrition, which occurs when a child's nutritional intake is insufficient for a long period of time. Stunting may have direct and indirect causes. Direct reasons include inadequate nutrition, while indirect causes include parenting. Food consumption is a habit that improves the body's nutritional state in a measurable way. Objective: This research is to determine the relationship between food intake and maternal parenting patterns with the incidence of stunting in toddlers at the Romana Clinic in 2024. Method: Quantitative, observational, cross-sectional techniques were used in this research. The months June to July 2024 were used for this research. Primary data and secondary data are two categories of data. Data were analyzed using the chi-square test for bivariate and univariate analysis.Research results: These findings show a significant correlation (p value = 0.000 <0.05) between food consumption and the incidence of stunting. P value = 0.002 <0.05, indicating a relationship between maternal parenting and the incidence of stunting.Conclusion: There is a strong correlation between calorie consumption and stunting. Parental involvement is significantly related to stunting levels. Suggestion: We hope that posyandu cadres and community health center officials in the study locations gain a deeper appreciation of the role parents play in monitoring the dietary needs of their toddlers.